Indigenous landscapes: of mind, spirit and place - Scharf, Lee, speaker; Unidentified speaker (Colorado State University. Libraries, 2011)
Worldwide, Indigenous Peoples such as Native American nations, participate in collaborative processes with national, state, local agencies, and other Indigenous Peoples as they address conservation and natural resource management issues. At the same time, many Indigenous Peoples have their own traditional dispute resolution histories, current decision making and conflict resolution practices, and legal systems. This Second Cohort Fellows Project sought to understand the use of collaborative processes in conservation practice by Native American nations throughout the continental U.S., both environmentally and culturally. Issues of collaborative conservation practice were identified and it was found that Native American nations have a determined interest in designing collaborative conservation methodologies appropriate to individual tribal decision making as part of developing their own customary law. By visiting over 100 tribal lands in person (and driving over 25,000 miles) and interviewing more than 200 Native Americans about collaborative conservation issues and practice, landscapes of mind, spirit and place emerged as vibrant and connected elements in a world seen differently. Finally, strategic contributions by tribal resource managers, judges, Native American lawyers, and tribal elders to the issues of conservation, resource management, and international law were seen to be deeply defined by a sense of place, a sense which is more than the simply obvious.
Presented at the Fall 2011 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Indigenous Peoples and Conservation", October 4, 2011, Colorado State University, Fort Collins, Colorado. This series focused on Indigenous Peoples and Conservation.
Lee Scharf is a Second Cohort Fellow at Colorado State University's Center for Collaborative Conservation, as well as a member of the CCC Executive Advisory Committee. She has a Masters' degree in Environmental Conflict Resolution and over twenty years' experience as a mediator working with tribal nations. Ms. Scharf's environmental conflict resolution taxonomy and annotated bibliography was published by the American Bar Association in 2002. She worked for the Environmental Protection Agency in Washington, DC from 1991 until 2006, first in the Superfund Enforcement program and then in the Office of General Counsel. From 2000 until 2006, Ms. Scharf was the National Tribal Mediation Lead for EPA through EPA's Conflict Prevention and Resolution Center. She helped create the Native Dispute Resolution Roster and program for the United States Institute for Environmental Conflict Resolution and serves on the Coordinating Committee for the USIECR Native Network. Currently, Ms. Scharf has her own business, Mediated Environmentally Sustainable Action (MESA), begun in 2004. Ms. Scharf lived on the Navajo Nation in Fort Defiance, Arizona from 1956-1959 and from that time on has respected the Navajo ways of viewing the world. Ms. Scharf has mediated cases in all environmental media with numerous other tribes around the country, most recently working with the Northern Arapaho tribe on the Wind River Indian Reservation in Wyoming and with Traditional Navajo communities at Black Mesa in Arizona.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: Native Hawaiian; conservation; resource management; Alaskan Native; tribal lands; Native American; international law